Liver transplantation. Issue 7 (July 2020) - Farid, Shahid
Abstract: Huge developments in the field of liver transplantation have occurred over the last 50 years. Improved immunosuppression regimens following the introduction of calcineurin-inhibitors, the development of novel organ preservation strategies, and enhanced perioperative care have resulted in 1-year survival rates of approximately 90%. The spectrum of disease now treated with liver transplantation has also grown to encompass a wide range of acute and chronic disease and hepatic malignancies. Early referral to specialist centres affords better outcomes for potential recipients and has prompted the development of specific scoring systems to objectively assess liver failure and guide organ allocation. The consistent gap between the number of recipients and availability of organs has driven many new developments such as split grafts and live donor transplantation. Use of the marginal graft is necessitated in many centres in an attempt to reduce the waiting list mortality. Here, we examine the origins and evolution of the speciality and describe some of the latest developments in the field of liver transplantation, with specific reference to current surgical techniques, evolving organ preservation technology and recent advances in associated medical therapies.